A selective critical review of financial accounting research. (February 2015) - Callen, Jeffrey
Abstract: This essay provides a selective critical review of the financial accounting literature focusing primarily on accounting valuation including implied costs of equity capital, empirical accounting proxies, and frictions in accounting theory. In the opinion of this author, accounting research in these areas is often too complacent, suffering from a lack of critical reasoning. Complacency distorts research innovation and hinders the long-run sustainability of accounting academe in the area of financial accounting. The examples discussed in this essay include (but are not limited to) the issue of structural modeling and model falsifiability; determining whether a firm is over or underpriced based on valuation models that do not allow for such phenomena; arbitrarily "merging" two disparate models one for valuation and one for the discount rate; failing to appreciate the empirical limitations induced by risk-neutral valuation models in estimating costs of capital; employing the same proxies over and over again that ostensibly have no underlying theoretical bases; estimating regressions that necessarily yield biased coefficients when the econometrics literature provides ready solutions; and generating complex models absent the frictions that are essential to the issue being researched.